Aging of infant formulas containing proteins from different sources. (December 2021) - Nunes, Lauane; Lima de Paula, Igor; Cristianini, Marcelo; Stephani, Rodrigo; Tavares, Guilherme M.
Abstract: Most infant formulas (IFs) use cow's milk-based ingredients as raw material. Nevertheless, to produce IFs for special needs, these raw materials may be replaced by other ones from different protein sources such as soy and rice. During transport and storage, IFs can be subjected to high temperatures, then, several physicochemical alterations may be accelerated. Even so, little is known about how the composition of IFs containing different protein sources may modulate their aging. Therefore, the objective of this work was to compare how different physicochemical parameters of IFs containing cow's milk, soy, or rice as major protein sources evolved during aging under different temperatures. Mild storage temperatures (3 °C and 25 °C) promoted little changes in the evaluated parameters. However, critical storage temperature (50 °C) (i) favored the faster development of the Maillard reaction in milk-IF and soy-IF; (ii) impaired their rehydration ability and (iii) favored the increase in the free fat content of rice-IF and soy-IF. This work is relevant in establishing parallels between different infant formulas that aim to meet the same nutritional demands of infants. Highlights: The glass transition is very low and easily reached for milk infant formula. Milk infant formula had sorption isotherm different from other formulations. Mild storage temperatures promoted little or no change in the evaluated parameters. Critical storage temperatures lead to a series of physical and chemical changes. Stability of infant formulas depends on their composition and storage temperature.